Direct synthesis of hydrogen peroxide on Pd nanosheets with edge decorated by Au nanoparticles - Hairui Liang; Yajie Tian; Bofeng Zhang; Li Wang; Guozhu Liu (Green Chemical Engineering, 2021)
Direct synthesis of hydrogen peroxide from hydrogen and oxide (DSHP) is considered as a green pathway for H2O2 production because of the simple reaction route and 100% theoretical atom efficiency. Here, 1.5 wt% Pd and 0.5 wt% Au were loaded on HZSM-5 nanosheets through sequential isovolumetric impregnation. TEM images and CO-TPD curves showed that Pd nanosheets were successfully synthesized between HZSM-5 nanosheets under zeolite confinement effect, and Au particles were loaded on the edge of Pd nanosheets and formed a structure that Pd nanosheets with edge decorated by Au nanoparticles (Au–Pd/ZN). The results showed that the selectivity for H2O2 could be reached around 60% in a 30 min reaction and the initial H2O2 productivity could reach 338.5 mmol gcat−1 h−1 on the Au–Pd/ZN catalyst. The enhanced selectivity and productivity could be related with high content of terrace sites and Au particles on the step sites of bimetallic nanosheets, in which both the terrace sites and the step sites replaced by Au particles showed higher dissociation activation energy for breaking the O–O bond than traditional step sites on Pd particles, inhibited the by-product reactions (2H2O2→2H2O​ + O2, 2H2 + O2→2H2O).